DIGITAL MARKETING STRATEGIES AND BUSINESS PERFORMANCE OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Kembara Sopather; Rahmat Anugerah; Normand Armando Lampe; Bismart Arituan (Count : Journal of Accounting, Business and Management, 2026)
Menstrual hygiene practices may affect urinary tract health, but evidence regarding the potential protective effect of herbal sanitary pads remains limited. This preliminary study examined differences in urinary leukocyte and nitrite findings after the use of herbal and non-herbal sanitary pads among women of reproductive age. A crossover intervention design was applied to 30 participants aged 18–25 years. Each participant used both types of sanitary pads during separate menstrual cycles, and fresh midstream urine samples were collected after menstruation. Urinary leukocytes and nitrites were assessed using a dipstick test. All participants showed leukocyte levels below 15 cells/µL after using herbal sanitary pads. Following the use of non-herbal sanitary pads, one participant had a leukocyte level above 15 cells/µL. Nitrite results were negative in all urine samples collected after both interventions. Statistical testing indicated no significant difference in leukocyte or nitrite findings between herbal and non-herbal sanitary pad use. These results suggest that herbal sanitary pads were associated with normal urinalysis profiles in all participants, although their preventive effect against urinary tract infection could not be confirmed. Further studies with larger samples and urine culture examination are needed to verify these findings.